Watak Asbab An-Nuzul Dalam Pendidikan Islam - Fitriani Nur Alifah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
Asbab An-Nuzul is a science to know the existence of causes and events concerning the background of a verse or several verses revealed by Allah, namely the verse of the Qur'an in the form of Allah's words. The Qur'an was revealed through the intermediary of the angel Gabriel revealed to the Prophet Muhammad. Asbab an-Nuzul aims to explain the wisdom of the provisions of the law and to specialize laws that are general in nature. al-Qur'an is a special foundation or a reference for Islamic community guidelines, by understanding the meaning of Asbab An-Nuzul, the community will be more able to add insight and understanding of the history of the Qur'an, besides that the community will better understand the origin of the verses revealed, in this case someone who understands the character of Asbab An-Nuzul someone will know how to apply and realize in everyday life and imitate him. Islamic education also examines the issue of Asbab an-Nuzul, because in understanding the verses of the Qur'an there are things that can be understood directly and some need explanations, therefore before understanding about Islamic education it is necessary to learn about the character or character of Asbab-an Nuzul first.